Market structure and bank competition conditions in five Asian countries - Abd Kadir, Hazlina (2013)
This study investigates the market structure of banking industry in five Asian countries from 1996–2009, using the most frequently applied measures of concentrations, the kbank concentration ratio (CRk) and the Herfindahl Hirschman Index (HHI). This thesis also evaluates the monopoly of banks over the fourteen years‘ period using the ‗Hstatistic‘, Panzar-Rosse approach. Panel data for commercial banks in Malaysia, Singapore, Thailand, Indonesia and the Philippines used in the study are extracted from the Bankscope database. The k-concentration ratio showed Singapore as a highly concentrated market. Malaysia and Thailand were moderately concentrated market, moving to a less concentrated one. Banks in Indonesia operated under a less concentrated market. For a robust result, the Herfindahl Hirschman Index was carried out to confirm the concentration conditions in these five Asian banks. The Herfindahl Hirschman Index result showed Singapore and the Philippines had highly concentrated banks. Singapore, on the other hand, showed a constant concentration ratio throughout the period. The concentration condition for the Philippines, meanwhile, had deteriorated. For Thailand, the concentration conditions had moved from highly concentrated to moderately concentrate despite having an increase in total number of banks in the country throughout the period. The Panzar-Rosse H-statistics suggested that banks in Singapore, Malaysia, Thailand, the Philippines and Indonesia were operating under monopolistic competition based on total interest income and total revenue as the dependent variables. In the long-run equilibrium, the Panzar-Rosse H-statistics suggested that Malaysia, Singapore, Thailand and the Philippines and Indonesia were operating under perfect competition.The findings of this study highlight the importance of size, efficient risk management and liquidity in sustaining long run revenue and competition. The results suggest that the countries with many small banks have limited capabilities to tap the market and are at the disadvantage compared to those countries with large banks. In the context of the five Asian countries in this study, most of the banks were relatively small judging from the amount of total asset as the benchmark. In order to compete in the next era of globalization, an ongoing investment in technological aspects related to banking products and services should be one of the essential policies for these banks to prosper. Merger and acquisitions should also be encouraged to strengthen the banks‘ financial positions. The policy direction should also be directed towards enhancing the resiliency, productivity and efficiency, risk management and liquidity of the financial institutions with the ultimate target of intensifying the robustness and stability of the banking sector.